Addendum on the scoring of Gaussian directed acyclic graphical models - Kuipers, Jack; Moffa, Giusi; Heckerman, David (Annal Statistics, 2014)
We provide a correction to the expression for scoring Gaussian directed acyclic graphical models derived in Geiger and Heckerman [Ann. Statist. 30 (2002) 1414–1440] and discuss how to evaluate the score efficiently.